Self‐Templated Hierarchically Porous Carbon Nanorods Embedded with Atomic Fe‐N4 Active Sites as Efficient Oxygen Reduction Electrocatalysts in Zn‐Air Batteries. (3rd December 2020) - Gong, Xiaofei; Zhu, Jianbing; Li, Jiazhan; Gao, Rui; Zhou, Qingyan; Zhang, Zhen; Dou, Haozhen; Zhao, Lei; Sui, Xulei; Cai, Jiajun; Zhang, Yunlong; Liu, Bing; et al.
Abstract: Iron‐nitrogen‐carbon materials are being intensively studied as the most promising substitutes for Pt‐based electrocatalysts for the oxygen reduction reaction (ORR). A rational design of the morphology and porous structure can promote the accessibility of the active site and the reactants/products transportation, accelerating the reaction kinetics. Herein, 1D porous iron/nitrogen‐doped carbon nanorods (Fe/N‐CNRs) with a hierarchically micro/mesoporous structure are prepared by pyrolyzing the in situ polymerized pyrrole on the surface of Fe‐MIL‐88B‐derived 1D Fe2 O3 nanorods (MIL: Material Institut Lavoisier). The Fe2 O3 nanorods not only partially dissolve to generate Fe 3+ for initiating polymerization but serve as templates to form the 1D structure during polymerization. Furthermore, the pyrrole coated Fe2 O3 nanorod architecture prevents the porous structure from collapsing and protects Fe from aggregation to yield atomic Fe‐N4 moieties during carbonization. The obtained Fe/N‐CNRs display exceptional ORR activities ( E 1/2  = 0.90 V) and satisfactory long‐term durabilities, exceeding those for Pt/C. Furthermore, the unprecedented Fe/N‐CNRs catalytic performance is demonstrated with Zn‐air batteries, including a superior maximum power density (181.8 mW cm −2 ), specific capacity (998.67 W h kg −1 ), and long‐term durability over 100 h. The prominent performance stems from the unique 1D structure, hierarchical pore system, high surface area, and homogeneously dispersed single‐atom Fe‐N4 moieties. Abstract : 1D iron/nitrogen (Fe/N)‐doped hierarchically porous carbon nanorods (Fe/N‐CNRs) catalysts with atomically dispersed Fe‐N4 sites are prepared via an in situ polymerization strategy. The obtained Fe/N‐CNRs catalyst displays excellent catalytic performance towards oxygen reduction reaction and Zn‐air batteries, surpassing commercial Pt/C, which indicates that the prepared catalyst possesses the potential of practical application in electrochemical devices.